Localization of a submarine groundwater source at the eastern coast of Black Sea, Georgia, using radio-tracing techniques - Patiris, D. L.; Schübert, M.; Eleftheriou, G.; Androulakaki, E. G.; Pappa, F. K.; Melikadze, G.; Kapanadze, N.; Tsabaris, C. (HNPS Advances in Nuclear Physics, 2019)
In this work the results of a preliminary study are presented concerning the localization of a submarine groundwater discharge diffusive source at the coastal area of Georgia, Eastern Black Sea. The results were obtained during the first cruise campaign along the Georgian coastline during the October 2012 in the frame of an on-going FP7 BS-ERA.NET project. Measurements of radon gas 222Rn were accomplished in seawater samples by means of an on-site radon measurement method. The samples were collected along two trajec- tories, parallel to the coast, of a total length of 35km. In the same samples conductivity measurements were supplementary accomplished. Where radon exhibited local maxima and conductivity local minima, seabed surface sediment samples were collected for subsequent radioactivity measurements by High Purity Germanium detector. As groundwater tracer the excess of 210Pb in the sediment samples was used. Combining the results from the seawater and sediment, a part of the initial trajectory - with length of 800m - was revealed as a potential area of submarine groundwater discharge diffusive source